CRGD-functionalized redox-sensitive micelles as potential doxorubicin delivery carriers for αvβ3 integrin over expressing tumors. Issue 112 (28th October 2015) - Cai, Meng; Ye, Mengyuan; Shang, Xingxing; Sun, Honghao; Liu, Mingxing; Sun, Hongmei; Ma, Zhuo; Zhu, Hongda
Abstract : The cRGD-modified redox-sensitive micelles as nanocarrier-based drug delivery provide an innovative platform for targeted integrin over expressing tumor cells anticancer drug delivery and offer better antitumour activity. Abstract : Polymeric micelles as nanocarrier-based drug delivery systems provide an innovative platform for selectively delivering active molecules and offer better antitumour activity. However, circulation stability in vivo, controllable drug intracellular release and high targeting efficiency are several practical challenges for micelles. Therefore, we developed cRGD-modified and shell crosslinked micelles (RSCMs) based on amphiphilic poly(styrene- co -maleic anhydride) (SMA). RSCMs exhibited a spherical shape and were homogeneous with an average diameter of 106.1 nm and a low polydispersity of 0.087. In comparison, after crosslinking the micelles possessed better stability against dilution and stronger redox-response towards dithiothreitol (DTT). The SMA micelles displayed high drug loading capacity for hydrophobic DOX with a drug loading of approximately 14.1–19.2% (w/w) and an encapsulation efficiency of 72.1–82.7% (w/w). The in vitro release studies of shell crosslinked micelles showed that DOX release was minimal (<25%, 24 h) under physiological conditions. However, in the presence of 10 mM DTT, accelerated release of DOX was achieved (60%, 24 h). MTT assays in B16F10 cells indicated that RSCMs displayed low cytotoxicity up to a concentration of 500 μg ml −1 . Moreover, the IC50 value showed that cRGD-DOX-ss-M could be more effective than other groups. In vitro, cellular uptake was further studied with confocal laser scanning microscopy and flow cytometry, both the qualitative and quantitative results demonstrated that cRGD-DOX-ss-M possessed much better specificity to cancer cells and superior stimulated release property in cytoplasm. Notably, cRGD-DOX-ss-M could more efficiently be delivered to and release into the nuclei of αv β3 integrin over expressing tumor cell line (B16F10) than counterparts of integrin-deficient tumor cells (Hela). Thus, these cRGD-modified redox-sensitive micelles have appeared as a technology platform with great potential for targeted anticancer drug delivery and release for integrin over expressing tumor cells.